STUDY OF ANALGESIC AND ANTIDIARRHOEAL ACTIVITIES OF Sonneratia caseolaris (LINN.) LEAF AND STEM USING DIFFERENT SOLVENT SYSTEM. - Bokshi, Bishwajit; Zilani, Md.Nazmul Hasan; Malakar, Aparajita; Roy, Debendra Nath; Shilpi, Jamil Ahmad; Sadhu, Samir Kumar (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2013)
The different fractions of crude ethanol extract of leaf and stem of S. caseolaris (Linn.) (Sonneratiaceae) were screened for its analgesic and antidiarrhoeal activities. The different fraction of crude extract was obtained by using four different solvent systems. The different fractions of crude extract produced significant writhing inhibition in acetic acid induced writhing in mice at dose of 250 and 500mg/kg BW comparable to the standard drug diclofenac sodium at the dose of 25mg/kg BW. When tested for its antidiarrhoeal effects on castor oil induced diarrhea in mice, it increased mean latent period and decreased the frequency of defecation significantly at the dose of 250 and 500mg/kg BW comparable to the standard drug loperamide at the dose of 50mg/kg BW. The overall results tend to suggest the analgesic and antidiarrhoeal activities of the different fractions of crude extract. Both ethyl acetate fraction of stem and chloroform fraction of leaf have significant analgesic activity. Again between the two fractions of crude ethanol extract ethyl acetate fraction of S.caseolaris stem have most significant antidiarrhoeal activity.Key words: analgesic, antidiarrhoeal, S.caseolaris, diclofenac sodium, loperamide.